The impact of information warfare on social security within the framework of liberal democracy - Semenets-Orlova , Inna; Moshnin, Andriy; Chmyr, Yaroslav; Rodchenko, Igor; Oleksiienko, Oleksandra (Research Journal in Advanced Humanities, 2023)
This research emphasized the significance of myth in forming national consciousness and consolidating people during the formation of a democracy, using the example of democratic transition in Ukraine. The study examined the dynamics of Ukraine’s democratic transition, focusing on the constructed mythical images, their reliance on national archetypes, and the antinomy between life’s realities and the imposed ideology. The role of political reality, which encompassed both objective reality and a closed virtual reality with constructed simulacra signs, was also analyzed. The findings suggested that in the spectator society of the 21st century, with increasingly diverse connections, the intuitive-irrational type of world perception dominated, leading individual and social consciousness to simplify their world view. Yet, a unified statist conceptual picture of the world was not created using the mythical images constructed as opposed to Soviet ones in Ukraine’s democratic transition. Understanding the role of political myth as a carrier of information about society and a driving force behind changes in the political space can guide future analysis of democratic transition processes and inform decision-making in emerging democracies.